The 2018 AHA/ACC/AACVPR/AAPA/ABC/ACPM/ADA/AGS/APhA/ASPC/NLA/PCNA Guidelines on the Management of Blood Cholesterol in Diabetes - Goldberg, Ronald B.; Stone, Neil J.; Grundy, Scott M. (Diabetes care, 2020)
The American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines recently published its 2018 recommendations on management of LDL cholesterol (LDL-C) in people with diabetes. For primary prevention, moderate-intensity statin therapy is recommended for those aged 40–75 years, with a preference for high-intensity statin treatment for older subjects and for those with higher estimated risk or risk-enhancing factors following a patient-clinician discussion. Statin therapy may be reasonable in adults <40 years or >75 years of age where there is less evidence for benefit. For people with diabetes and established atherosclerotic cardiovascular disease, high-intensity statin therapy is recommended. The majority of these subjects have very high risk, and an LDL-C goal of <70 mg/dL is recommended. If this target is not achieved, ezetimibe and/or a proprotein convertase subtilisin/kexin type 9 inhibitor may be added.